(Invited) Issues with n-type Dopants in Germanium. (23rd July 2018) - Skarlatos, Dimitrios; Ioannou-Sougleridis, Vassilios; Barozzi, Mario; Pepponi, Giancarlo; Vouroutzis, Nikolaos Zisis; Velessiotis, Dimitrios; Stoemenos, John; Zographos, Nikolas; Colombeau, Benjamin P
Abstract : The last decade has seen considerable experimental and theoretical work towards the use of germanium for high-speed low-power electronics. Despite the demonstration of high performance p-channel Ge transistors in planar and non-planar device technology, fabrication of n-channel Ge transistors faces a number of scientific and technological challenges, which hinder the development of CMOS logic circuits based entirely on Ge. Major challenge constitutes the control of fast n-type dopant (out-/in-)diffusion in Ge, which prevents the formation of ultra-shallow and highly activated n + /p junctions necessary for n-channel Ge MOSFET's enhanced performance. The paper focuses on parameters affecting n-type dopant diffusion in Ge and the attempts to suppress it, with particular emphasis on the action of nitrogen as phosphorous diffusion blocker.